Curable polymer compound and resin composition containing the compound
Through the resin composition composed of polymer compounds of a specific structure and a radical initiator, the problem of insufficient dielectric properties and adhesion in the application of high-frequency circuit boards in the prior art is solved, and a thin film-like adhesive with low dielectric constant, low dielectric loss and high thermal stability is achieved.
Patent Information
- Application Number
- JP2021165622
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-07
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-10-07
AI Technical Summary
The polymer materials in the prior art are difficult to meet the low dielectric constant, low dielectric loss and high thermal stability simultaneously in high frequency circuit board applications, and their adhesion to copper foil is insufficient.
A resin composition composed of a polymer compound of a specific structure and a free radical initiator is used to form a thin film-like adhesive through a free radical reaction induced by heat or light energy. A resin composition composed of a polymer compound of a specific structure and a free radical initiator is used to form a thin film-like adhesive through a free radical reaction induced by heat or light energy, solving the problem of insufficient dielectric properties and adhesion in high-frequency circuit board applications in the prior art.
It achieves a polymer material with low dielectric constant, low dielectric loss and high thermal stability, with excellent adhesion and heat resistance, and is suitable for dielectric materials of high-frequency circuit boards.
Smart Images

Figure 0007628070000001 
Figure 0007628070000002 
Figure 0007628070000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer compound which can be easily formed into a film by casting a solution onto a substrate, which can undergo a thermal or photocuring reaction when used in combination with a radical initiator, and which produces a cured product having excellent dielectric properties, adhesiveness, and heat resistance. [Background technology]
[0002] Phenoxy resin is a polymeric compound with a very large molecular weight obtained by polymerizing a bifunctional epoxy resin and a bifunctional phenolic compound. By adding this phenoxy resin, general epoxy resin compositions and radically polymerizable compositions can be made into a film shape, so it is used in a wide range of fields as an important component of film-type adhesives, and is particularly used in the electrical and electronic fields for interlayer insulation layers of printed wiring boards and resin-coated copper foils. Although the cured product of the resin composition to which the phenoxy resin is added has excellent adhesiveness and film-forming ability, it has low heat resistance and high dielectric constant and dielectric loss tangent (dielectric constant of 3.5 and dielectric loss tangent of about 0.03 at a frequency of 1 GHz), and therefore cannot be used for electronic devices with a high signal response speed in recent years. Polymeric fluorine compounds such as polytetrafluoroethane (PTFE) (Patent Document 1) and liquid crystal polymers (Patent Document 2) are generally known as resins with excellent dielectric properties, but these resins have extremely low compatibility with other resins and insufficient adhesive properties. Patent Document 3 describes a bis(diallyl isocyanurate) compound obtained by reacting diallyl isocyanurate with a dihalogen compound, but the present inventor conducted follow-up tests and found that the cured product of the curable polymer compound obtained by the structural formula in the same document has a dielectric loss tangent of about 0.005 at 10 GHz, which does not fully meet the low dielectric properties required for current high-frequency circuit board applications. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-001274 A [Patent Document 2] JP 2014-060449 A [Patent Document 3] JP 2015-151413 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made in view of the above points, and has an object to provide a curable polymer compound that has sufficient flexibility to be formed into a film, has high adhesion to low-roughness copper foil, and has a low dielectric constant and dielectric tangent. [Means for solving the problem]
[0005] As a result of extensive investigations, the present inventors have found that the above problems can be solved by using a resin composition containing a polymer compound having a specific structure, and have completed the present invention. That is, the present invention is (1)The following formula (1)
[0006] [ka]
[0007] (wherein m and n are average values of the number of repeating units and each independently range from 1 to 2,000), (2) A resin composition comprising the polymer compound according to the above item (1) and a radical initiator. (3) The resin composition according to the above item (2), which contains a radical-reactive monomer having one or more radical-reactive functional groups in one molecule. (4) The resin composition according to the above item (2), which contains a radical-reactive polymer having two or more radical-reactive functional groups in one molecule. (5) A film-like adhesive comprising the resin composition according to any one of (2) to (4) above, and (6) A cured product of the resin composition according to any one of the preceding items (2) to (4) or the film-like adhesive according to the preceding item (5). Regarding. Effect of the Invention
[0008] The polymer compound according to the present invention and a resin composition containing the same can be cured by using a radical initiator in combination with heat or light energy, and the cured product of the resin composition can provide a polymer compound having excellent dielectric properties, adhesion, heat resistance and water resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described. The polymer compound of the present invention represented by the above formula (1) is a dehydrochlorination condensation product of the chloromethyl groups of a random copolymer of chloromethylstyrene and styrene and 1,3-diallyl isocyanurate. In addition, in formula (1), the structure of the polymer compound is represented by the average number of repeating units of the unit derived from styrene and the unit derived from chloromethylstyrene and 1,3-diallyl isocyanurate. However, the polymer compound of the present invention is formed by randomly bonding m units derived from styrene and n units derived from chloromethylstyrene and 1,3-diallyl isocyanurate (both m and n are average values), and the following formula (2) in this specification is also represented with the same intention.
[0010] Examples of chloromethylstyrene, which is a raw material for random copolymers, include 4-chloromethylstyrene and 2-chloromethylstyrene.
[0011] The method for copolymerizing chloromethylstyrene with styrene is not particularly limited as long as it is a known copolymerization method, and examples thereof include bulk polymerization, solution polymerization, emulsion polymerization, and suspension polymerization. Solvents that can be used in solution polymerization include toluene, xylene, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, propylene glycol monomethyl ether acetate, N-methylpyrrolidone, N,N-dimethylformamide, and γ-butyrolactone. Emulsion polymerization and suspension polymerization usually use water and a surfactant, and the copolymerization reaction is carried out in a state where the raw material components are emulsified or suspended in water.
[0012] The copolymerization reaction may be any of radical polymerization, cationic polymerization, and anionic polymerization. In the case of radical polymerization, it is preferable to use a radical polymerization initiator. Specific examples of the radical polymerization initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile, 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, hydrogen peroxide, di-t-butyl peroxide, dicumyl peroxide, and benzoyl peroxide. The amount of the radical polymerization initiator is usually 0.001 to 5 parts by mass per 100 parts by mass of the raw material components of the copolymer. The polymerization temperature is usually 50 to 250° C., preferably 60 to 200° C., and the polymerization time is usually 0.5 to 30 hours, preferably 1 to 20 hours. The radical polymerization reaction is preferably carried out under a nitrogen gas atmosphere to prevent polymerization inhibition by oxygen in the air.
[0013] Specific examples of cationic polymerization initiators include inorganic acids such as sulfuric acid and hydrochloric acid, organic acids such as CF3COOH and CCl3COOH, and super strong acids such as CF3SO3H and HClO4. Specific examples of anionic polymerization initiators include butyl lithium, Na-naphthalene complexes, alkali metals, alkyl lithium compounds, sodium amides, Grignard reagents, and lithium alkoxides. However, since there is a concern that the ionic initiators used in cationic polymerization and anionic polymerization remain in the copolymer even after the polymerization reaction and adversely affect the dielectric properties and insulating properties, it is preferable to synthesize the copolymer that is the intermediate raw material of the polymer compound of the present invention by radical polymerization. The amount of the cationic polymerization initiator or anionic polymerization initiator is usually 0.01 to 5 parts by mass per 100 parts by mass of the raw materials for the copolymer. The polymerization temperature is usually 40 to 150° C., preferably 50 to 120° C., and the polymerization time is usually 0.5 to 20 hours, preferably 1 to 15 hours.
[0014] After polymerization, the unreacted styrene is removed by heating under reduced pressure, or by pouring the reaction mixture into a poor solvent to precipitate only the polymer, thereby removing the unreacted styrene.
[0015] The following formula (2) is a structural formula of a random copolymer of chloromethylstyrene and styrene, and m and n in formula (2) have the same meanings as m and n in formula (1). As the compound represented by formula (1) of the present invention (a compound having a structure represented by formula (1)), a polymer compound represented by the above formula (1) using a copolymer represented by the following formula (2) as an intermediate raw material is preferred.
[0016] [ka]
[0017] The random copolymer serving as an intermediate material for the polymer compound of the present invention usually has a number average molecular weight of 3,000 to 300,000, and preferably 5,000 to 200,000. In order to obtain a copolymer having a number average molecular weight within the above range, it is preferable to adjust the amount of initiator used during copolymer synthesis to an appropriate amount.The amount of initiator required to obtain a copolymer having a weight average molecular weight within the above range depends on the type of solvent and the amount of chloromethylstyrene compound and styrene used in copolymerization reaction, so it cannot be generally stated, but it is generally known that a copolymer having a large molecular weight can be obtained by reducing the amount of initiator, and it is sufficient to select the amount of initiator that can obtain a copolymer having a desired molecular weight within the above range of the amount of initiator.
[0018] The ratio of the chloromethylstyrene compound and styrene used when synthesizing the random copolymer that is the intermediate raw material of the polymer compound of the present invention is not particularly limited, but the amount (mass) of styrene used is usually 4 to 99.5 times, preferably 4.5 to 99.7 times, the mass of chloromethylstyrene. By setting the ratio of the chloromethylstyrene compound and styrene used as the raw materials of the copolymer within the above range, the polymer compound of the present invention can be obtained whose cured product exhibits excellent dielectric properties (low dielectric constant and low dielectric loss tangent).
[0019] The polymer compound of the present invention can be obtained by subjecting the chloromethyl groups of the random copolymer to a dehydrochlorination reaction with 1,3-diallyl isocyanurate in the presence of a carbonate salt.
[0020] Specific examples of the carbonate include alkali metal carbonates such as lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, and cesium carbonate, alkaline earth metal carbonates such as magnesium carbonate, calcium carbonate, strontium carbonate, and barium carbonate, alkali metal bicarbonates such as lithium bicarbonate, sodium bicarbonate, potassium bicarbonate, rubidium bicarbonate, and cesium bicarbonate, alkaline earth metal bicarbonates such as magnesium bicarbonate, calcium bicarbonate, strontium bicarbonate, and barium bicarbonate, and ammonium salts such as ammonium carbonate and ammonium bicarbonate. In the present invention, the carbonate is not limited to the above examples. The carbonates may be used alone or in combination of two or more. The carbonate is used in an amount of 1 mole or more, preferably 1.5 moles or more, per mole of 1,3-diallyl isocyanurate.
[0021] By using an iodide together with the carbonate, the reaction between 1,3-diallyl isocyanurate and the dihalogen compound can be accelerated.
[0022] As the iodide, for example, alkali metal iodides such as lithium iodide, sodium iodide, potassium iodide, etc. can be mentioned as preferred examples. However, in the present invention, the iodide is not limited to the above, and various metal salts other than the above, such as copper iodide, can also be mentioned as preferred examples. In the present invention, the above iodide is usually used in the range of 0.005 to 3 molar parts, preferably 0.01 to 0.30.5 molar parts, relative to 1 equivalent of chloromethyl group in the random copolymer.
[0023] The reaction between 1,3-diallyl isocyanurate and the random copolymer, which is an intermediate raw material, is carried out in a reaction solvent. The reaction solvent is not particularly limited as long as it does not inhibit the above reaction, and examples thereof include aromatic hydrocarbons such as benzene, toluene, and xylene, halogenated hydrocarbons such as methylene chloride, chloroform, carbon tetrachloride, chlorotrifluoromethane, dichloroethane, chlorobenzene, and dichlorobenzene, ethers such as diethyl ether, diisopropyl ether, tetrahydrofuran, dioxane, dimethoxyethane, and diethylene glycol dimethyl ether, amides such as formamide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and hexamethylphosphorotriamide, and sulfoxides such as dimethyl sulfoxide. These reaction solvents can be used alone or in combination of two or more.
[0024] The reaction between 1,3-diallyl isocyanurate and the random copolymer, which is an intermediate raw material, is usually carried out at a temperature in the range of 0 to 200°C, preferably in the range of 80 to 130°C, depending on the solvent used in the reaction, and the reaction time is usually in the range of about 30 minutes to 48 hours. The target polymer compound can be obtained by reacting 1,3-diallyl isocyanurate with a random copolymer, which is an intermediate raw material, in a reaction solvent in the presence of the carbonate (and the iodide) under heating, filtering the resulting reaction mixture to remove undissolved matter, and concentrating the resulting filtrate.
[0025] The number average molecular weight of the polymer compound of the present invention thus obtained is preferably in the range of 11,000 to 300,000, more preferably 15,000 to 200,000. If the molecular weight is smaller than the above range, the adhesion to low-roughness copper foil will be low, and if it is larger, the viscosity will be high, which may make coating, etc. difficult. In this specification, the molecular weight refers to a value calculated in terms of polystyrene based on the results of GPC measurement.
[0026] The resin composition of the present invention contains the polymer compound of the present invention and a radical initiator. Preferred thermal radical initiators include peroxides such as benzoyl peroxide, cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, di-t-butyl peroxide, t-butylcumyl peroxide, α,α-bis(t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, dicumyl peroxide, di-t-butylperoxyisophthalate, t-butylperoxybenzoate, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di(trimethylsilyl)peroxide, and trimethylsilyltriphenylsilylperoxide.
[0027] Examples of preferred photoradical initiators include benzoin and its alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, and 1,1-dichloroacetophenone; anthraquinones such as 2-methylanthraquinone, 2-amyl anthraquinone, 2-t-butyl anthraquinone, and 1-chloro anthraquinone; thioxanthones such as 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, and 2-chlorothioxanthone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzophenones such as benzophenone; 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propan-1-one and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1; acylphosphine oxides, and xanthones.
[0028] The content of the radical initiator in the resin composition of the present invention is usually 0.1 to 10 parts by mass, preferably 0.1 to 8 parts by mass, per 100 parts by mass of the polymer compound and the resin components such as the optional radical reactive monomer described below.
[0029] The resin composition of the present invention may be used in combination with a radical reactive monomer. By using a radical reactive monomer in combination, the reactivity of the resin composition of the present invention and the heat resistance of the cured product can be improved. The radical reactive monomer in the present invention means a compound having one or more radical reactive functional groups in one molecule and having a number average molecular weight of 500 or less (the lower limit of the number average molecular weight is about 100). Specific examples of radical reactive monomers include acenaphthylene, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, neopentyl glycol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, glycerin dimethacrylate, 2-hydroxy-3-acryloyloxypropyl methacrylate, and ethylene oxide adduct of bisphenol A. acrylate, trimethylolpropane trimethacrylate, tricyclodecane dimethanol dimethacrylate, glycerin dimethacrylate, trimethylolpropane trimethacrylate, ethoxylated isocyanuric acid triacrylate, ε-caprolactone modified tris-(2-acryloxyethyl) isocyanurate, pentaerythritol triacrylate, ditrimethylolpropane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, pentaerythritol tetraacrylate, dipentaerythritol erythritol polyacrylate, dipentaerythritol hexaacrylate, triallyl isocyanurate, triallyl cyanurate, divinylbenzene, divinyl isophthalate, N-phenyl-maleimide, N-phenyl-methylmaleimide, N-phenyl-chloromaleimide, Np-chlorophenyl-maleimide, Np-methoxyphenyl-maleimide, Np-methylphenyl-maleimide, Np-nitrophenyl-maleimide, Np-phenoxyphenyl-maleimide, Np-phenylaminophenyl-maleimide, Np-phenoxycarbonylphenyl-maleimide, 1-maleimido-4-acetoxysuccinimide-benzene, 4-maleimido-4'-acetoxysuccinimide-diphenylmethane, 4-maleimido-4'-acetoxysuccinimide-diphenyl ether, 4-maleimido-4'-acetamido-diphenyl ether, 2-maleimido-6-acetamido-pyridine, 4-maleimido-4'-acetamido-diphenylmethane and Np-phenylcarbonylphenyl-maleimide, N-ethylmaleimide, N-2-maleimide.Examples of the functional group include 6-xylylmaleimide, N-cyclohexylmaleimide, N-2,3-xylylmaleimide, xylylmaleimide, 2,6-xylenemaleimide, and 4,4'-bismaleimide diphenylmethane, and the like. Of these, those having a maleimide group as a functional group are preferred. These radical reactive monomers may be used alone or in combination of two or more.
[0030] The resin composition of the present invention may be used in combination with a radical reactive polymer. By using a radical reactive polymer in combination, the adhesiveness of the resin composition of the present invention and the heat resistance of the cured product can be improved. The radical reactive polymer in the present invention means a compound having one or more, preferably two or more radical reactive functional groups in one molecule and having a number average molecular weight of 500 or more. Specific examples of radical reactive polymers include copolymers of styrene and butadiene, or modified polyphenylene ether resins, or imide-extended bismaleimides.
[0031] The copolymer of styrene and butadiene, which is a radical reactive polymer, may be a random copolymer or a block copolymer. The ratio of styrene to butadiene in the polymer is usually 10:90 to 90:10, and the number average molecular weight is usually 1,000 to 10,000. Specific product examples include Ricon 100, Ricon 181, and Ricon 184 from Cray Valley.
[0032] The modified polyphenylene ether resin, which is a radical reactive polymer, is preferably a compound having a methacryloyl group, an acryloyl group, or a vinyl group at both ends of the molecule and a number average molecular weight of 1,000 to 10,000. Specific examples include a compound represented by the following formula (3) having a methacryloyl group at both ends and a number average molecular weight of about 1,700 (product name SA9000, manufactured by SABIC Japan LLC), and a compound represented by the following formula (4) having a vinyl group at both ends and a number average molecular weight of about 1,200 or 2,200 (product name OPE-2St 1200 or OPE-2St 2200, manufactured by Mitsubishi Gas Chemical Co., Inc.).
[0033] [ka]
[0034] [ka]
[0035] The imide-extended bismaleimide resin, which is a radical reactive polymer, can be obtained by a known method described in, for example, Japanese Patent Publication No. 5328006. Specifically, it can be obtained by carrying out a dehydration condensation reaction of an aliphatic diamine and an aromatic or aliphatic tetracarboxylic dianhydride in an organic solvent using an acid catalyst in a molar ratio in which the aliphatic diamine is in excess, followed by dehydration condensation of the amino groups present in the polymer terminals with maleic anhydride, and removing the catalyst by washing with water.
[0036] Specific examples of aliphatic diamines include 1,10-diaminodecane; 1,12-diaminododecane; dimer diamine; 1,2-diamino-2-methylpropane; 1,2-diaminocyclohexane; 1,2-diaminopropane; 1,3-diaminopropane; 1,4-diaminobutane; 1,5-diaminopentane; 1,7-diaminoheptane; 1,8-diaminomenthane; 1,8-diaminooctane; 1,9-diaminononane; 3,3'-diamino-N-methyldipropylamine; diaminomaleonitrile; 1,3-diaminopentane; and 9,10-diaminophenanthrene, with dimer diamine being particularly preferred.
[0037] Specific examples of aromatic or aliphatic tetracarboxylic dianhydrides include pyromellitic anhydride, 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 3,4,9,10-perylene tetracarboxylic dianhydride, bicyclo(2.2.2)oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, diethylenetriaminepentaacetic dianhydride, ethylenediaminetetraacetic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 2,2'-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, and 4,4'-bisphenol A. Diphthalic anhydride, 5-(2,5-dioxytetrahydro)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, ethylene glycol bis(trimellitic anhydride), hydroquinone diphthalic anhydride, 1,2,3,4-cyclobutane tetracarboxylic dianhydride (CBDA), 1,2-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,1'-bicyclohexane-3,3',4,4'-tetracarboxylic dianhydride Examples of suitable dianhydrides include tetracarboxylic acid-3,4:3',4'-dianhydride, 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic acid anhydride, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic acid dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic acid dianhydride, 2,3,4,5-tetrahydrofuran tetracarboxylic acid dianhydride, and 3,5,6-tricarboxy-2-norbornane acetic acid dianhydride, but pyromellitic anhydride and 1,2,4,5-cyclohexane tetracarboxylic acid dianhydride are particularly preferred. A specific product name is BMI-3000 by Designer Molecules, Inc.
[0038] The resin composition of the present invention may be used in combination with an organic solvent. Specific examples of the organic solvent include aromatic solvents such as toluene and xylene, ether solvents such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monomethyl ether monoacetate, and propylene glycol monobutyl ether, ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone, lactones such as γ-butyrolactone and γ-valerolactone, amide solvents such as N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide, and N,N-dimethylimidazolidinone, and sulfones such as tetramethylene sulfone. The content of the organic solvent in the resin composition of the present invention is usually 90% by mass or less, preferably 30 to 80% by mass in the resin composition.
[0039] The resin composition of the present invention may be used in combination with a polymerization inhibitor to improve storage stability. The polymerization inhibitor that can be used in combination is not particularly limited as long as it is a generally known one, and examples thereof include quinones such as hydroquinone, methylhydroquinone, p-benzoquinone, chloranil, and trimethylquinone, aromatic diols, and di-t-butylhydroxytoluene.
[0040] The resin composition of the present invention can be used by blending fillers and additives in amounts that do not impair the inherent performance, for the purpose of imparting desired performance depending on the application. The fillers may be in the form of fibers or powders, and examples of such fillers include silica, carbon black, alumina, talc, mica, glass beads, and glass hollow spheres.
[0041] The resin composition of the present invention can also be used in combination with a flame-retardant compound, an additive, and the like. These are not particularly limited as long as they are commonly used. For example, flame-retardant compounds include bromine compounds such as 4,4-dibromobiphenyl, phosphate esters, melamine phosphate, phosphorus-containing epoxy resins, nitrogen compounds such as melamine and benzoguanamine, oxazine ring-containing compounds, silicon-based compounds, and the like. Additives include ultraviolet absorbers, antioxidants, photopolymerization initiators, fluorescent brighteners, photosensitizers, dyes, pigments, thickeners, lubricants, defoamers, dispersants, leveling agents, gloss agents, and the like, and can be used in appropriate combination as desired.
[0042] The resin composition of the present invention can be used by coating or impregnating it onto various substrates. For example, when a thermal radical initiator is used, it can be used as an interlayer insulating layer of a multilayer printed circuit board by coating it onto a PET film, as a coverlay by coating it onto a polyimide film, or as a resin-coated copper foil by coating it onto copper foil and drying it. It can also be used as a printed wiring board or a prepreg for CFRP by impregnating it into glass cloth, glass paper, carbon fiber, various nonwoven fabrics, etc. Furthermore, it can also be used as various resists by using a photoradical initiator.
[0043] The interlayer insulating layer, coverlay, resin-coated copper foil, prepreg, and the like of the present invention can be heated and pressurized in a hot press or the like to form a cured product. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples and comparative examples, although the present invention is not limited to these examples.
[0045] Example 1 (Synthesis of the polymer compound of the present invention) (Step 1) Synthesis of a random copolymer (copolymer 1) represented by the following formula (5) A flask equipped with a thermometer, a cooling tube, a nitrogen gas inlet tube, and a stirrer was charged with 98.47 parts of styrene, 1.53 parts of 4-chloromethylstyrene, 0.05 parts of azobisisobutyronitrile, and 40 parts of toluene, and reacted for 7 hours at 125°C under a nitrogen atmosphere to obtain a toluene solution of copolymer 1 represented by the following formula (5). 50 parts of dimethyl sulfoxide were added to this toluene solution, and toluene, unreacted styrene, and a part of dimethyl sulfoxide were distilled off under heating and reduced pressure. The above-mentioned "addition of dimethyl sulfoxide and distillation of the solvent under heating and reduced pressure" was repeated four more times to obtain 120 parts of a dimethyl sulfoxide solution of a random copolymer. When this solution was analyzed by gas chromatography, toluene and styrene were not present. A part of this solution was heated under reduced pressure, and the amount of copolymer 1 calculated as the solid content based on the dry mass was 70.2 parts. Considering that the amount of unreacted styrene was 28.27 parts, the obtained random copolymer was a copolymer of 70.47 parts of styrene and 1.53 parts of 4-chloromethylstyrene. The number average molecular weight of the sample used to calculate the dry mass was 92,000 and the weight average molecular weight was 245,000. From the copolymerization ratio and number average molecular weight of 4-chloromethylstyrene, the value of n in formula (5) is calculated to be 869 and the value of m is calculated to be 13.
[0046] [ka]
[0047] (Step 2) Synthesis of the polymer compound of the present invention (polymer compound 1) represented by the following formula (6) Dimethyl sulfoxide was further added to the dimethyl sulfoxide solution of copolymer 1 obtained in step 1 to adjust the concentration of copolymer 1 to 20% by mass, and then 2.07 parts of potassium carbonate, 0.166 parts of potassium iodide, and 2.09 parts of 1,3-diallyl isocyanurate were added and reacted for 8 hours at 110 ° C. under stirring. The reaction solution was pressure filtered through a filter paper with a capture particle size of 1 μm to remove solids such as generated salts, and the filtrate was once distilled off with a rotary evaporator to remove excess dimethyl sulfoxide, and then dimethyl sulfoxide was added again to obtain 288 parts of a dimethyl sulfoxide solution containing 25% by mass of the polymer compound of the present invention (polymer compound 1) represented by the following formula (6). The number average molecular weight of the obtained polymer compound 1 was 93,000, and the weight average molecular weight was 247,000.
[0048] [ka]
[0049] Example 2 (Preparation of Resin Composition of the Present Invention) To 10 parts of the dimethyl sulfoxide solution of the polymer compound 1 of the present invention obtained in Example 1, 0.05 parts of dicumyl peroxide as a radical initiator was added and mixed uniformly to obtain a resin composition 1 of the present invention.
[0050] Example 3 (Preparation of Resin Composition of the Present Invention) To 10 parts of a dimethyl sulfoxide solution of the polymer compound 1 of the present invention obtained in Example 1, 0.05 parts of dicumyl peroxide as a radical initiator and 0.5 parts of a butadiene-styrene copolymer Licon 100 (manufactured by Cray Valley Chemical Industries, Ltd.) were added and mixed uniformly to obtain a resin composition 2 of the present invention.
[0051] Example 4 (Preparation of Resin Composition of the Present Invention) To 10 parts of a dimethyl sulfoxide solution of the polymer compound 1 of the present invention obtained in Example 1, 0.05 parts of dicumyl peroxide as a radical initiator and 0.5 parts of modified polyphenylene ether resin SA-9000 (manufactured by Sabic LLC) were added and mixed uniformly to obtain a resin composition 3 of the present invention.
[0052] Example 5 (Preparation of Resin Composition of the Present Invention) To 10 parts of a dimethyl sulfoxide solution of the polymer compound 1 of the present invention obtained in Example 1, 0.05 parts of dicumyl peroxide as a radical initiator and 0.5 parts of imide-extended bismaleimide resin BMI-3000 (manufactured by Designer Molecules, Inc.) were added and mixed uniformly to obtain a resin composition 4 of the present invention.
[0053] (Evaluation of dielectric properties of cured resin composition) Resin compositions 1 to 4 of the present invention obtained in Examples 2 to 5 were applied to a thickness of 280 μm on the mirror surface of a copper foil having a thickness of 18 μm using an applicator, and the solvent was dried by heating at 90° C. for 10 minutes to provide a film-like adhesive on the copper foil. The film-like adhesive on the copper foil obtained above was heated and cured at 180° C. for 1 hour using a vacuum oven, and then the copper foil was removed by immersing it in an etching solution. Since a cured product having a thickness of 70 μm that could be handled as a film was obtained from the film-like adhesive made of the resin composition of Examples 2 to 5, the dielectric properties were evaluated using the cured product obtained above. The dielectric properties were evaluated based on the results of measuring the dielectric constant and dielectric loss tangent at 10 GHz by a cavity resonance method using a network analyzer 8719ET (manufactured by Agilent Technologies). The results are shown in Table 1.
[0054] (Evaluation of Adhesive Strength of Cured Resin Composition) The resin compositions 1 to 4 of the present invention obtained in Examples 2 to 5 were applied to a matte surface of a 12 μm thick, high frequency low roughness copper foil (CF-T4X-SV: manufactured by Fukuda Metal Foil Powder Co., Ltd.) to a thickness of 50 μm using an applicator, and the solvent was dried by heating at 90° C. for 10 minutes to obtain a copper foil having a film-like adhesive made of the resin composition of the present invention. The matte surface of the same copper foil as above was placed on the adhesive surface of the copper foil obtained above, and the copper foil was heated and cured for 1 hour at a pressure of 3 MPa in a vacuum press, and the 90° peel strength (adhesive strength) between the copper foils was measured using an autograph AGX-50 (manufactured by Shimadzu Corporation). The results are shown in Table 1. The laminated copper foil was also cut into 3 cm squares and floated in a solder bath at 288° C. to measure the time until abnormalities such as blistering and peeling occurred on the copper foil.
[0055] [Table 1]
[0056] As described above, the polymer compound of the present invention can be cured in the presence of a radical initiator to form a flexible film, and the cured product exhibits excellent dielectric properties, adhesiveness, and heat resistance.
Claims
1. The following formula (1) 【Chemistry 1】 (wherein m and n are average values of the number of repeating units and each independently range from 1 to 2,000).
2. A resin composition comprising the polymer compound according to claim 1 and a radical initiator.
3. The resin composition according to claim 2, comprising a radical-reactive monomer having one or more radical-reactive functional groups in one molecule.
4. The resin composition according to claim 2, which comprises a radical reactive polymer having two or more radical reactive functional groups in one molecule.
5. A film-like adhesive comprising the resin composition according to any one of claims 2 to 4.
6. A cured product of the resin composition according to any one of claims 2 to 4 or the film-like adhesive according to claim 5.
Citation Information
Patent Citations
Production of fine spherical resin particles
JP1995018008A
Fluoroplastic copper-clad laminate and manufacturing method thereof
JP2005001274A
Novel polymerizable monomer, photosensitive composition comprising the same and lithographic printing plate
JP2007045736A
High frequency circuit board
JP2014060449A
Method for producing bis(diallyl isocyanurate) compound
JP2015151413A